2022
DOI: 10.3390/diagnostics12102408
|View full text |Cite
|
Sign up to set email alerts
|

A Host-Directed Approach to the Detection of Infection in Hard-to-Heal Wounds

Abstract: Wound infection is traditionally defined primarily by visual clinical signs, and secondarily by microbiological analysis of wound samples. However, these approaches have serious limitations in determining wound infection status, particularly in early phases or complex, chronic, hard-to-heal wounds. Early or predictive patient-derived biomarkers of wound infection would enable more timely and appropriate intervention. The observation that immune activation is one of the earliest responses to pathogen activity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Also, wounds exudates, fluid circulation, drug degradation by host cells and bacteria, and the controlled release properties of our hydrogels, constantly dilute and inactivate a large portion of PHMB from the wound. 41–43…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, wounds exudates, fluid circulation, drug degradation by host cells and bacteria, and the controlled release properties of our hydrogels, constantly dilute and inactivate a large portion of PHMB from the wound. 41–43…”
Section: Resultsmentioning
confidence: 99%
“…Also, wounds exudates, fluid circulation, drug degradation by host cells and bacteria, and the controlled release properties of our hydrogels, constantly dilute and inactivate a large portion of PHMB from the wound. [41][42][43] Swelling properties of hydrogels were assessed due to their importance in maintaining wound moisture and enhancing healing processes. 44 Results (Figure 1E) suggested that dressings utilizing MACF or MAC were able to absorb high levels of liquids which implies their ability to draw bacteria away from the wounds by entrapping wound fluids and bacteria.…”
Section: Hydrogel Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation